New power converter topology for low power rotary capacitive power transfer system - Yusmarnita Yusop (2018)
Since the past decade, many researchers have taken interest to investigate the capacitive power transfer (CPT) as an alternative to achieve contactless power transfer. By employing the electric field as the energy transfer medium, CPT has the advantages of the confined electric field between coupling plates, power transfer capability through metal barriers, low eddy current power losses associated with metal surroundings, as well as the potential to minimise circuit size and cost. This thesis mainly concentrates on the development of a fundamental theory of CPT system and its application for low power contactless charging. Initially, the thesis begins by analysing the Class-E resonant inverter performance to generate high frequency AC power source to drive the CPT system. Due to the sensitivity of components variation, the investigation of Class-E resonant inverter with feedback frequency controller unit is proposed to enhance the efficiency of CPT system by preserving the zero voltage switching (ZVS) condition over a longer distance. Second, the utilization of compensation network to serve as an impedance converter in order to enable efficient power transfer between two stages with non-matching impedances had been investigated. Here, mathematical analysis of the sensitivity of the system output power in respect to the load variation was introduced. Third, a Class-E combined with LCCL compensation network topology for both transmitter and receiver is proposed to provide impedance matching and hence, keeping the ZVS condition for wider load-range changes. Next, based on the proposed Class-E LCCL topology, a single plate rotary CPT system was developed to realize power transfer to the rotating load. Finally, in enhancing the capacitive coupler embedded in the rotary CPT system, the rotating capacitive coupler was upgraded with multiple plate structure approach to generate a small and compact capacitive coupler plate without the need of increasing electric field emission. This was controlled by a novel power flow control topology called cascaded Boost-Class-E. With the application of these proposed control methods, the output power of rotary CPT system could be adjusted. Overall, this thesis presents a fundamental study on CPT technology carried out by employing mathematical analysis, computer simulations, and practical experiments for validation purpose. A 10W prototype was constructed to verify the proposed circuit. The best experiment prototype of this work has demonstrated more than 90% efficiency at 2 mm working distance, which can be considered as an exceptional performance, when compared to the existing low power scale CPT system achievements. In conclusion, the research outcomes portray the feasibility and the potential of CPT as an emerging contactless power transfer solution, as well as the theory and the practical design methods that establish a solid foundation for future CPT research and development.